2015
DOI: 10.1111/wrr.12282
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enzyme analysis as a diagnostic tool for wound infection: Comparison between clinical judgment, microbiological analysis, and enzyme analysis

Abstract: In clinical practice, diagnosis of wound infection is based on the classical clinical signs of infection. When infection is suspected, wounds are often swabbed for microbiological culturing. These methods are not accurate (clinical judgment in chronic wounds) or provide results after several days (wound swab). Therefore, there is an urgent need for an easy-to-use diagnostic tool for fast detection of wound infection, especially in chronic wounds. This study determined the diagnostic properties of the enzymes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…This popular threshold of 10 5 CFU has been used as a critical criterion for diagnosis of infection in chronic wounds, reasoning on the induction of local tissue damage in the wound because of the increase in the levels of bacterial‐related toxins and inflammatory mediators . Historically, the bacterial load at ≥10 5 CFU per one gram of tissue that was obtained from wound swabbing, biopsy, or ≥ 10 5 CFU/mL wound fluid can be seen as an indicator for wound infection . However, this bacterial load has been shown not to be accurate in diagnosing infection as there may be some bacteria with high virulence levels, especially when they have microbial synergy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This popular threshold of 10 5 CFU has been used as a critical criterion for diagnosis of infection in chronic wounds, reasoning on the induction of local tissue damage in the wound because of the increase in the levels of bacterial‐related toxins and inflammatory mediators . Historically, the bacterial load at ≥10 5 CFU per one gram of tissue that was obtained from wound swabbing, biopsy, or ≥ 10 5 CFU/mL wound fluid can be seen as an indicator for wound infection . However, this bacterial load has been shown not to be accurate in diagnosing infection as there may be some bacteria with high virulence levels, especially when they have microbial synergy.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the prospective study by Cooper et al compared the bacterial load using three different techniques to obtain samples (swab, fluid, and biopsy), and found that the bacterial load depended on the wound size and the duration of the wound; as the highest bacterial load was found in the largest and the longest ulcers . In a prognostic study with a primary aim of evaluating the diagnostic properties of three enzymes identified from wound fluid of 81 patients with acute or chronic wounds (11 CLUs), Blokhuis‐Arkes et al examined the relationship between clinical and microbiological diagnosis of infection and found no relationship between the clinical judgement and microbiological results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More objective measurements such as laboratory and/ or validated physical criteria for snakebite wound infections should be established in the future. 36 The judicious use of antibiotics based on local bacterial patterns should be considered to improve the management of N. atra bite wound infections. Chen and others inspected 21 snakebite cases with wound infections and isolated at least 17 bacterial species from these wounds, including 17 caused by N. atra, one by T. stejnegeri, one by P. mucrosquamatus, and two by unknown snake species.…”
mentioning
confidence: 99%
“…Early infection diagnosis and management are important for diabetics, yet diagnosis may be delayed because local signs and symptoms of infection are often diminished in a DFI because of concomitant peripheral neuropathy and PAD . However, a close correlation between neutrophil‐derived enzymes and wound infection status was reported in a clinical study involving 81 patients, of which 42% were diabetic …”
Section: Infection Managementmentioning
confidence: 99%